UPAYA MAHASISWA BK UNTUK MENGEMBANGKAN KETERAMPILAN KONSELING - Vanny Anggraini; Yeni Karneli; Mudjiran Mudjiran (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Basic counseling skills are skills that counselors have in capturing or responding to statements and communicating them again in carrying out individual counseling services. Students must be able to apply and master basic counseling skills because it can more or less guarantee the continuity of a counseling process to achieve counseling goals. The purpose of this study was to find out how students' efforts to develop counseling skills, the scope of this study was BK students of Padang State University in 2017, was in the fifth semester totaling 155 students, with the consideration that they were conducting BK labor counseling engineering classes, which developed counseling skills. The method used in this research is descriptive qualitative. Summary of the results of the results in this study are counseling skills that are done by students doing peer counseling, to be able to develop their skills and conduct counseling analysis by analyzing video counseling between counselor and client in conducting counseling so that they are able to do counseling professionally